Treatment coverage rates for refractive error in the National Eye Health survey - Foreman, Joshua (PLoS One, 2017)
OBJECTIVE: To present treatment coverage rates and risk factors associated with uncorrected refractive error in Australia. METHODS: Thirty population clusters were randomly selected from all geographic remoteness strata in Australia to provide samples of 1738 Indigenous Australians aged 40 years and older and 3098 non-Indigenous Australians aged 50 years and older. Presenting visual acuity was measured and those with vision loss (worse than 6/12) underwent pinhole testing and hand-held auto-refraction. Participants whose corrected visual acuity improved to be 6/12 or better were assigned as having uncorrected refractive error as the main cause of vision loss. The treatment coverage rates of refractive error were calculated (proportion of participants with refractive error that had distance correction and presenting visual acuity better than 6/12), and risk factor analysis for refractive correction was performed. RESULTS: The refractive error treatment coverage rate in Indigenous Australians of 82.2% (95% CI 78.6–85.3) was significantly lower than in non-Indigenous Australians (93.5%, 92.0–94.8) (Odds ratio [OR] 0.51, 0.35–0.75). In Indigenous participants, remoteness (OR 0.41, 0.19–0.89 and OR 0.55, 0.35–0.85 in Outer Regional and Very Remote areas, respectively), having never undergone an eye examination (OR 0.08, 0.02–0.43) and having consulted a health worker other than an optometrist or ophthalmologist (OR 0.30, 0.11–0.84) were risk factors for low coverage. On the other hand, speaking English was a protective factor (OR 2.72, 1.13–6.45) for treatment of refractive error. Compared to non-Indigenous Australians who had an eye examination within one year, participants who had not undergone an eye examination within the past five years (OR 0.08, 0.03–0.21) or had never been examined (OR 0.05, 0.10–0.23) had lower coverage. CONCLUSION: Interventions that increase integrated optometry services in regional and remote Indigenous communities may improve the treatment coverage rate of refractive error. Increasing refractive error treatment coverage rates in both Indigenous and non-Indigenous Australians through at least five-yearly eye examinations and the provision of affordable spectacles will significantly reduce the national burden of vision loss in Australia.